BET 1: The Ottawa Subarachnoid Hemorrhage Clinical Decision Rule shows high sensitivity but limited evidence of patient benefit. Issue 8 (20th July 2021) - Law, Dorothy; Hirst, Robert; Horner, Daniel
Abstract : A short-cut review of the literature was carried out to examine the diagnostic test characteristics and potential patient benefits through the use of the Ottawa Subarachnoid Haemorrhage Clinical Decision Rule. Nine papers were identified as suitable for inclusion using the reported search strategy. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of the best papers are tabulated. It is concluded that the Ottawa Clinical Decision Rule has a high sensitivity for the diagnosis of subarachnoid haemorrhage; however, there is limited robust evidence of international generalisability and no evidence of improved patient outcomes following implementation. Further prospective research is required in populations with variable prevalence to evaluate the safety and effectiveness of this intervention, compared with routine evaluation strategies.